Epicardial and transverse sinus fat pad near left atrium appendage; role of 3D echocardiography. Issue 4 (14th December 2020) - Mohseni‐badalabadi, Reza; Sahebjam, Mohammad; Mohseni‐badalabadi, Mehdi; Hosseini, Kaveh
Abstract: Pericardial fat pad in transverse sinus adjacent to left atrial appendage (LAA) is a rare condition that may resemble LAA thrombosis especially in suspected cases. More Trans‐esophageal echocardiography (TEE) angulations and also 3D TEE images are helpful tools to confirm the diagnosis. Abstract : Pericardial fat pad in transverse sinus adjacent to left atrial appendage (LAA) is a rare condition that may resemble LAA thrombosis especially in suspected cases. More Trans‐esophageal echocardiography (TEE) angulations and also 3D TEE images are helpful tools to confirm the diagnosis.